Of Dreams and Denials: The Imagined History in Mahasweta Devi’s Draupadi and Mother of 1084 - Pramanik P. (My University, 2025)
This article aims to discuss the role played by women participants in the Naxalbari movement through a study of Mahasweta Devi’s works. The position of women within a male dominated movement and their fate once they are in police captivity following their arrest has been examined. The article tries to map the differences of experiences of women Naxalites of the rural and urban areas. There has been scholarly intervention which has established the major role played by women in the movement; however, the question of women’s representation and interpretation of the movement remains largely unexplored. Considering the third world women’s engagement with feminism the article attempts to study the subordination and expression of dissent within the framework of the movement and beyond it. It also tries to understand the alternative nonviolent modes of protest that women chose to register their dissent. © 2024 South Asian Literary Association.